2018
DOI: 10.1111/jdi.12807
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and acceptability of continuous glucose monitoring for type 2 diabetes management: A narrative review

Abstract: The present narrative review discusses the role of continuous glucose monitoring (CGM) in glycemic and weight control, and lifestyle behavior adherence in adults with type 2 diabetes. A literature search from January 2001 to November 2017 was carried out (MEDLINE, CINAHL, Web of Science and Scopus). Eligible studies were trials evaluating the use of CGM with the aim of achieving glucose control or lifestyle‐related treatment adherence over a period of ≥8 weeks in adults with type 2 diabetes compared with usual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 58 publications
1
48
0
1
Order By: Relevance
“…While persistent daily use of rtCGM is considered essential for intensive insulin management, [1][2][3][9][10][11][12][13][14] clinical trials and recent meta-analyses have reported the value of rtCGM use in individuals with T2D independent of their treatment regimen. [15][16][17][18] The realworld data included in this report add to the growing body of evidence indicating that intermittent rtCGM use with less intensive treatment regimens is associated with significant glycemic improvements, [19][20][21] creates valuable teaching opportunities 22 and is effective in promoting desired self-care behaviors. 20 Our study has some limitations.…”
Section: Discussionmentioning
confidence: 84%
“…While persistent daily use of rtCGM is considered essential for intensive insulin management, [1][2][3][9][10][11][12][13][14] clinical trials and recent meta-analyses have reported the value of rtCGM use in individuals with T2D independent of their treatment regimen. [15][16][17][18] The realworld data included in this report add to the growing body of evidence indicating that intermittent rtCGM use with less intensive treatment regimens is associated with significant glycemic improvements, [19][20][21] creates valuable teaching opportunities 22 and is effective in promoting desired self-care behaviors. 20 Our study has some limitations.…”
Section: Discussionmentioning
confidence: 84%
“…There are a few other aspects of CGM which are worth exploring in future research, such as pregnant users' acceptability and effect on GWG and glycemic control. In our review, only two studies surveyed user acceptability and accuracy of CGM (18, 36), while several studies have been done in patients with T2D with high compliance rates (>90%) (43). Therefore, more should be done on pregnant women, especially on those with GDM, in order to implement universal application of CGM during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The Journal of Clinical Endocrinology & Metabolism; Copyright 2019 DOI: 10.1210/jc.2019-00031 was shown that hormonal profiles are needed in order to effectively monitor and adjust glucocorticoid treatment [23]. From this perspective, CAH is similar to type 1 diabetes, where studies involving continuous glucose monitoring have demonstrated better patient outcomes associated with the number of self-managed blood glucose measurements throughout the day [24,25]. Thus, we are tempted to speculate that there is a need for more suitable tests allowing for more frequent measurement of more specific adrenal steroid hormones in patients with CAH and that such an approach might improve health outcomes if they lead to more frequent adjustments of treatment or more accurate glucocorticoid treatment.…”
Section: Discussionmentioning
confidence: 99%